1968
DOI: 10.1149/1.2411269
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Formation of Thin Oxide Layers on Nickel

Abstract: It could be demonstrated that the initial period of oxidation of nickel at 400 ~ and 500~ is governed by a logarithmic rate law. However, after approximately 5 hr at 400~ and 1 hr at 500~ the rate of oxidation changes into a fourth power rate law ruling in a special oxide-thickness region. This rate law can be understood if a negative space charge, caused by nickel-ion vacancies, in the growing NiO layer is assumed and if the current of nickelion vacancies from the surface of the oxide layer to the metal-oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1970
1970
1979
1979

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…5 and 6). 1 As mentioned earlier various rate laws have been previously reported for nickel oxidation at 400~176 including parabolic (2), two stage logarithmic (3,4), and logarithmic followed by fourth power (5). We would consider that the variety of results arise from the development of structurally different oxides whose formation has been influenced by the nature of the starting surface.…”
Section: Initial Stage--evaporated Metal Films Have Beenmentioning
confidence: 92%
“…5 and 6). 1 As mentioned earlier various rate laws have been previously reported for nickel oxidation at 400~176 including parabolic (2), two stage logarithmic (3,4), and logarithmic followed by fourth power (5). We would consider that the variety of results arise from the development of structurally different oxides whose formation has been influenced by the nature of the starting surface.…”
Section: Initial Stage--evaporated Metal Films Have Beenmentioning
confidence: 92%
“…GaAs electrodes have been the subject of various electrochemical studies (1)(2)(3)(4). It has been shown that the basic anodic process in aqueous electrolytes is the anodic dissolution of the GaAs electrode (2) whereas the cathodic process is mainly due to hydrogen evolution (2,4). The first process occurs via the valence band, i.e., holes are consumed.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the equilibrium condition ~ #idni = 0 to Eq. [4] it can be shown, after some algebra, that the oxygen partial pressure, pa, in the presence of a stress is related to the stress-lree value, Pdiss., by…”
Section: And Noting That [M]/[m] ~ = [Vo"]/[vo"] ~mentioning
confidence: 99%
See 1 more Smart Citation
“…More complex are the conditions for the formation of thin tarnish layers (d < 103 A) in the range of low and medium temperatures, because in the first stages of surface film growth the effects of surface and space charges as well as of nucleation and recrystallization processes must be considered (HAUFBE, SCHOTTKY; CABRERA, MOTT; EVANS). The kinetics of the tarnish oxidation has been studied by a number of authors a t several metals in a wide range of temperatures and pressures (EVANS; N w o~o , UHLIG; WEISSMANTEL 1962, HAUFFE 1968. Mainly following time laws for layer formation have been observed and interpreted, however, usually they only give an accurate description of the real behaviour within limited ranges of time and temperature.…”
Section: Introductionmentioning
confidence: 99%